Essential anesthesiology for healthcare professionals - Mohamed, Rozilah @ Abdul Hadi; Osman, Ariff; Md Ralib, Azrina; Mat Nor, Mohd Basri; Lukman, Mohd Fahmi; Yahaya, Azura Sharena; Abdullah, Nor Zamzila (Department of Anaesthesiology and Intensive Care, 2012)
Anaesthesiology is one of the fields that is poorly understood by the healthcare professional in particular or the public in general. This is the result of it being too specialized or too difficult to comprehend. With current fast growing medical developments and knowledge, it has become difficult to understand certain concepts in this field. As lecturers and anaesthesiologists, it is our intention to close this gap so that this field is much more interesting to learn. This book is not only focused on the undergraduate students but it can also be used in clinical practice where relevant by medical officers